Long-term results of an endoscopic screening program for superficial esophageal cancer in patients with head and neck squamous cell carcinoma - Nobre Moura, Renata; Kuboki, Yeda; Baba, Elisa Ryoka; Safatle-Ribeiro, Adriana; Martins, Bruno; de Paulo, Gustavo Andrade; Tolentino, Luciano Lenz; de Lima, Marcelo Simas; Kulcsar, Marco Aurelio; Sallum, Rubens Antonio Aissar; Ribeiro, Ulysses, Jr.; Maluf-Filho, Fauze (Endoscopy International Open, 2022)
Background and study aims Patients with head and neck squamous cell carcinoma (HNSCC) are at risk of a second primary tumor in the gastrointestinal tract, most commonly in the esophagus. Screening these patients for esophageal carcinoma may help detect asymptomatic dysplasia and early cancer, thus allowing curative treatment and more prolonged survival, but the impact of endoscopic screening remains uncertain. Here we aimed to describe the long-term results of an esophageal SCC screening program in patients with head and neck cancer in terms of prevalence, associated risk factors, and survival.Patients and methods We performed an observational study of a prospectively collected database including patients with HNSCC who had undergone high-definition endoscopy with chromoscopy between 2010 and 2018 at a Brazilian tertiary academic center.Results The study included 1,888 patients. The esophageal SCC prevalence was 7.9 %, with the majority (77.8 %) being superficial lesions. Significant risk factors for esophageal high-grade dysplasia (HGD) and invasive cancer included tumors of the oral cavity and oropharynx and the presence of low-grade dysplasia (LGD). Overall survival (OS) was significantly shorter among patients in whom esophageal cancer was diagnosed at an advanced stage (P < .001). OS did not significantly differ between patients with HGD and early esophageal cancer versus those without esophageal cancer (P = .210) Conclusions Endoscopic screening for superficial esophageal neoplasia in patients with HNSCC improves esophageal cancer detection. Screening could potentially benefit patients with primary cancer located at the oropharynx or oral cavity. In addition, the detection of esophageal LGD indicates a need for endoscopic surveillance.